Effects of annealing temperature and time on decrepitation of lump coals and characteristics of resultant coal chars. Issue 5 (6th July 2017) - Zhang, Shengfu; Qiu, Shuxing; Peng, Haijun; Sun, Chenggong; Wen, Liangying; Xu, Jian; Bai, Chenguang
Abstract: The decrepitation of two Chinese lump coals was investigated using high‐temperature fast pyrolysis in a purpose‐designed furnace to simulate the reaction conditions in the coal‐based Corex ironmaking process, and evolution of functional group, porosity, crystallite structure as well as CO2 reactivity of resultant coal chars was characterized. The results demonstrate that the decrepitation index varied significantly for different coal samples and their particle sizes, because of the variable thermal stress induced. The decrepitation index increased with increasing temperature and particle size, and severe decrepitation was observed when coal particles were increased to 20 mm. The coal chars derived from Xinglongzhuang lump coal at different temperatures had much more developed macroporous structure than Datong lump coal chars. A significant change of the crystallite height demonstrated a great influence of temperature on carbon structure. The CO2 reactivity of coal chars decreased with increasing annealing time at different temperatures examined, but the effect of carbonization temperatures on their reactivity has the opposite behavior, which is related to the porosity development and carbon structure variation. The interrelations of these phenomena further suggest that the appropriate dome temperature is crucial for ensuring permeability of coal char bed in Corex except for coal type. Copyright © 2017 Curtin University of Technology and John Wiley & Sons, Ltd. © 2017 Curtin University of Technology and John Wiley & Sons, Ltd.